Analisis Keberlanjutan Pengolahan Kerupuk Ikan di Kabupaten Ogan Ilir, Sumatera Selatan - Fadel Wahyu Setiofano; Herpandi Herpandi; Indah Widiastuti (Jurnal FishtecH, 2017)
The purpose of this research was to assess the status of sustainability from fish ckerekers processing house hold in Ogan Ilir by a multy-dimensional system. The sustainability analysis used a modification method of Rapid Appraisal for Fisherier (RAPFISH). This research used a survey method to read a fact that occurs in location. The visit and interview have been done by using, structure quisionnaires. The data proced as a tabulation and a analised by descriftive method. As a result, the sustainability status of ckerekers processing in ogan ilir was less sustainable, wich indeks value was 2.29. From all dimension, the marketing dimension was the highest indeks value that means enough sustainable. In other hand, the technology dimension was the lower value of sustainable indeks, with status s was not sustainable.